House for sale at 40 South 12th Street - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a Victorian style house at 40 South Twelfth Street, San Jose with a detached garage in the background. A sign on the overhang has the number 40. A sign in the window reads "For sale." A sign on the lawn reads "For sale. Biebrach, Bruch & Moore. 26 W. San Antonio, CY 2-7241."